Effects of Project Based Learning Model Assisted by Picture Media on Advertising Text Writing Skills - Sihombing, Vera Ironita Christiani; Iswara, Prana Dwija (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
In the 2013 curriculum implementation module, it is explained that Project Based Learning is a learning model that uses projects/activities as the core of learning. Students explore, judgments, interpretations, synthesis, and information to produce various learning form. This research was conducted to determine the effectiveness of Project Based Learning with the help of picture media on the skills of writing ad text. The scope of this research is writing ad text skills with the help of picture media. This study uses a quantitative approach with a pre-experimental method, one group pre-test post-test design. The population of this study was elementary school students of class V. The sample was determined by simple random sampling technique. The process of collecting data by assigning students to write ad text. The data analysis technique used is the Wilcoxon test. The results of the data analysis showed that there were differences in the writing skills of fifth grade elementary school students using picture media and without using picture media. Then it can be proven that picture media has a higher effect than conventional methods on the ability to write advertising text